2004
DOI: 10.1213/01.ane.0000096190.36875.67
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Versus Manual Ventilation via a Face Mask During the Induction of Anesthesia: A Prospective, Randomized, Crossover Study

Abstract: In this model of apneic patients with an unprotected airway, pressure-controlled ventilation resulted in reduced inspiratory peak flow rates and lower peak airway pressures when compared with circle system ventilation, thus providing an additional patient safety effect during face-mask ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Our data are comparable to those previously reported by von Goedecke et al [7] in which he showed that pressurecontrolled ventilation resulted in reduced inspiratory peak flow rates and peak airway pressures when compared with manual circle system ventilation. However, to our knowledge, there were no studies that compared the respiratory effects of pressure-controlled ventilation in apnoeic patients to manual and volume-controlled ventilation during induction of anaesthesia.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are comparable to those previously reported by von Goedecke et al [7] in which he showed that pressurecontrolled ventilation resulted in reduced inspiratory peak flow rates and peak airway pressures when compared with manual circle system ventilation. However, to our knowledge, there were no studies that compared the respiratory effects of pressure-controlled ventilation in apnoeic patients to manual and volume-controlled ventilation during induction of anaesthesia.…”
Section: Discussionsupporting
confidence: 92%
“…In this study a controlled environment was used during induction of anaesthesia [11,12]. When compared to facemask ventilation using a standard Esmarch manoeuvre, a nasopharyngeal, or an oropharyngeal airway, the Jaw-Thrust-Device was more effective in reducing airway resistance and thus increasing expiratory tidal volumes during pressure-controlled facemask ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilator settings for reoxygenation are shown in Figure 4. Two studies have compared handheld ventilators to BVMs for non-intubated ventilations; these studies have shown the handheld ventilator to be safe and that it may be associated with fewer complications (25,26). The improved valve structure and more precise settings of a standard rather than handheld ventilator make it even more desirable.…”
mentioning
confidence: 99%